PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUASAN PELANGGAN FOODPEDIA CEMPAKA PUTIH JAKARTA PUSAT - Adit Fikriansyah; Syahrul Reza; Hanuna Shafariah (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study airned to determine the effect of service qualities and locationson customer satisfactions of Foodpedia Cempaka Putih, Central Jakarta. This study used a quantitativeresearch by distributing questionnaires to 110 accidential sampling of respondents. The results showed that bassed on hypothesis testing using the T-test, service qualities andlocations has a positive and significant results on customer satisfactions. Meanwhile, using the F-test, all the independent variables in this study has a significant effect on customer satisfactions. The effect of service qualities (X1) and locations (X2) on customer other variables which not examined in this study.